If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5y + 6)(9y + 7) = 0 Reorder the terms: (6 + 5y)(9y + 7) = 0 Reorder the terms: (6 + 5y)(7 + 9y) = 0 Multiply (6 + 5y) * (7 + 9y) (6(7 + 9y) + 5y * (7 + 9y)) = 0 ((7 * 6 + 9y * 6) + 5y * (7 + 9y)) = 0 ((42 + 54y) + 5y * (7 + 9y)) = 0 (42 + 54y + (7 * 5y + 9y * 5y)) = 0 (42 + 54y + (35y + 45y2)) = 0 Combine like terms: 54y + 35y = 89y (42 + 89y + 45y2) = 0 Solving 42 + 89y + 45y2 = 0 Solving for variable 'y'. Factor a trinomial. (6 + 5y)(7 + 9y) = 0Subproblem 1
Set the factor '(6 + 5y)' equal to zero and attempt to solve: Simplifying 6 + 5y = 0 Solving 6 + 5y = 0 Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 5y = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 5y = 0 + -6 5y = 0 + -6 Combine like terms: 0 + -6 = -6 5y = -6 Divide each side by '5'. y = -1.2 Simplifying y = -1.2Subproblem 2
Set the factor '(7 + 9y)' equal to zero and attempt to solve: Simplifying 7 + 9y = 0 Solving 7 + 9y = 0 Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 9y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 9y = 0 + -7 9y = 0 + -7 Combine like terms: 0 + -7 = -7 9y = -7 Divide each side by '9'. y = -0.7777777778 Simplifying y = -0.7777777778Solution
y = {-1.2, -0.7777777778}
| (3n-2)10=35 | | 3x/2+1/5=3x/5+1/2 | | 6x-1=4x+4 | | 9=3y+5 | | x^2+8x-330=0 | | -8r-7=-24 | | -36=2(x-4) | | 6x+12=30 | | 7x+2=3x+10 | | 20-5n=n+2 | | 4x^2*2x*12=0 | | 15-n=4 | | 4x^2*2x*12= | | 3(8-6n)=24 | | 2x+3=+7 | | 3n+1=n+3 | | 10+2n=0 | | 15-2n=19 | | 5n=200 | | 6n+11=5 | | 5x+29.75=3.25 | | 4n+1=3 | | 35x^2+9x-2=0 | | 10x+5=5x+10+5 | | 2n-3=27 | | 10x+5=5x+10 | | 5n+1=11 | | 7x+6=10x | | 8x+18=2x+174 | | 119-6x=21x+20 | | -98-10x=20-17x | | -6(36-10b)+8=12 |